Suppliers as Stewards? Managing Social Standards in First- and Second-Tier Suppliers - ZAMANTILI NAYIR, DİLEK (SPRINGER, 2016)
Buyer-supplier relationships are often framed as principal-agent relationships, based on contractual arrangements that temporarily align the goals of both parties. The underlying notion is that the relationship between buyers and suppliers is adversarial in nature and that the supplier, acting in the role of the agent, will take advantage of the principal if not sufficiently controlled. We propose that there is empirically also another type of partnership which reflects the propositions of stewardship theory. According to this theory, suppliers are motivated to work autonomously towards contractually agreed objectives. We analyse how the agency and stewardship theories differ regarding their descriptions of autonomy, motivation, identification, authority, stakeholder orientation and short- versus long-term collaboration. We analyse the case of a first-tier supplier and four second-tier suppliers situated in Turkey in the area of Istanbul which collaborate with the aim of improving their social and environmental performance. The results show that the relationship between the partners in this case has become more collaborative over time and can now be described in terms of stewardship theory rather than in terms of agency theory. We conclude that the distinction between agency and stewardship relationships is empirically meaningful in the context of supplier-buyer relationships and adds a new aspect to our understanding of how to achieve more sustainable supply chains.
Keywords: Sustainable supply chain management; Textile industry; Agency theory; Stewardship theory; Auditing; Social and environmental standards; CHAIN MANAGEMENT; AGENCY THEORY; ORGANIZATIONAL ECONOMICS; GOVERNANCE; ETHICS; RESPONSIBILITY; COLLABORATION; COMMUNICATION; PERFORMANCE; LEADERSHIP